Corrosion of plasma sputtering medium entropy alloy thin film: A multidisciplinary perspective. (15th May 2023) - Chuang, Kai-Chi; Chang, Yu-Yen; Chiang, Ching-Yu; Liu, Yun-Chung; Hung, Hao-Hsuan; Tseng, Ko-Kai; Yeh, Jien-Wei; Cheng, Hsiu-Wei
Abstract: Plasma sputtering multi-principal element alloys (MPEAs) thin film is critical to functional multi-layer material design for a wide range of applications. To investigate its electrochemical stability, we established a multidisciplinary approach including in-situ optical microscope integrated EC-SPR coupled with ICPMS, and ex-situ XPS and XAS analysis. Compared to our previous work in bulk material, we observed a significant reactivity change of plasma sputtering thin film on gold. Based on XPS, XAS and SPR results, we propose that the formation of Cr ( OH ) 3 at the edge and the interface between alloys and gold layers is responsible for weakening the corrosion resistance of an NiCoCr/Au system. Highlights: Multidisciplinary investigation of plasma sputtering medium entropy alloy thin film corrosion. Hard X-ray application in non-destructive thin film analysis. Application of Surface Plasmon Resonance in study solid–solid interfacial interaction. Addition of Fe in the studied alloys is crucial in stabilizing the Cr oxide passive layer. EC-Microscope-ICPMS home-built setup for thin film corrosion study in real-time.